A Metagenome Diversity Profile of Springs Microbial for Oligotroph Springs Assessment in UB Forest - Viky Vidayanti; Catur Retnaningdyah; Endang Arisoesilaningsih; Feri Eko Hermanto (International Journal Bioautomation, 2025)
Ecosystem quality is an emergent property of a complex system that interacts between biotic and abiotic factors. The study aims to determine the bacterial community profile of several springs with different surrounding ecosystems. Metagenomic analysis using next-generation sequencing (NGS) is performed to determine the microbial profile, taxa richness, and relative abundance of spring water from Buk Bejat (BB), Sumber Dampul (SD) 1, 2, and 3, respectively. The community profile of spring water bacteria at the phylum level shows the same pattern in all study areas. Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidota are the dominant phyla in all sites. At the family level, Comamonadaceae is the most plentiful family in all study sites, along with Lactobacillales P5D1-392, which is found to have a low frequency in SD2 and SD3 compared to SD1 and BB. On the other hand, Muribaculaceae, Morganellaceae, Bacteroidaceae, Oscillospiraceae, Bifidobacteriaceae, Saccharimonadaceae, and Peptostreptococcaceae are found with higher frequency in SD2 and SD3 compared to BB and SD1. The hierarchical clustering at the family level shows two closely related clusters composed of the ecosystem, BB-SD1, and SD2-SD3, but this cluster is not followed by bacterial beta diversity. The alpha diversity in BB and SD1 is higher than in SD2 and SD3 based on ACE, Chao1, Margalef, and Simpson indexes.